2014
DOI: 10.1128/jcm.01370-14
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Virulence-Locus Sequence Typing of Staphylococcus lugdunensis Generates Results Consistent with a Clonal Population Structure and Is Reliable for Epidemiological Typing

Abstract: cStaphylococcus lugdunensis is an emergent virulent coagulase-negative staphylococcus responsible for severe infections similar to those caused by Staphylococcus aureus. To understand its potentially pathogenic capacity and have further detailed knowledge of the molecular traits of this organism, 93 isolates from various geographic origins were analyzed by multi-virulence-locus sequence typing (MVLST), targeting seven known or putative virulence-associated loci (atlL R2 , atlL R3 , hlb, isdJ, SLUG_09050, SLUG_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 65 publications
3
16
0
Order By: Relevance
“…This latter method allowed us to define nearly the same number of profiles as MLST and was consistent with MLST, as unique STs or their single locus variants (SLVs) and double locus variants (DLVs) were found in each VT T group. Thus, this comparison confirms the coevolution of virulence-associated loci studied with housekeeping genes as shown previously 17 , and validates the use of the trilocus method as a good epidemiological tool while significantly reducing costs.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This latter method allowed us to define nearly the same number of profiles as MLST and was consistent with MLST, as unique STs or their single locus variants (SLVs) and double locus variants (DLVs) were found in each VT T group. Thus, this comparison confirms the coevolution of virulence-associated loci studied with housekeeping genes as shown previously 17 , and validates the use of the trilocus method as a good epidemiological tool while significantly reducing costs.…”
Section: Discussionsupporting
confidence: 85%
“…lugdunensis clinical isolates by MLST and MVLST. Data for 20 isolates were derived from our previous studies 16 , 17 , while we performed MLST and MVLST analysis of 108 additional clinical isolates for the purposes of the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, both housekeeping and virulence genes were found to be evolving under purifying selection as suggested by d N / d S ratios and the negative values of Tajima’s D statistic. This finding is not without precedent, since similar results have been reported for Listeria monocytogenes 36 and Staphylococcus lugdunensis 32 . Hence, aside from preserving the most fit pathotype clones, purifying selection might also contribute to maintain gene sequences that define a given pathotype.…”
Section: Discussionsupporting
confidence: 81%
“…By contrast, and as expected, the average of haplotype diversity of 0.61 found in M. hominis housekeeping genes was comparable to other mycoplasmas species, such as Mycoplasma bovis (average of 0.64) 17 and Mycoplasma hyorhinis (average of 0.651) 30 . Previous studies have confirmed that virulence gene-based typing schemes (MVLST) afford higher resolution than did MLST, making them the best surrogate approaches to carry out reliable epidemiological investigations 31 , 32 . However, neither MVLST nor MLST data could be unambiguously correlated with the clinical status of the studied strain collections.…”
Section: Discussionmentioning
confidence: 97%